Does outpatient physical therapy with the aim of improving health-related physical fitness influence the level of physical activity in patients with long-term musculoskeletal conditions?. Issue 3 (September 2015) - Holm, I.; Tveter, A.T.; Moseng, T.; Dagfinrud, H.
Abstract Objective To evaluate any change in self-reported level of physical activity in patients receiving a general physical exercise programme in addition to disease-specific physiotherapy treatment. Design Pre–post-intervention study. Setting Outpatient physiotherapy clinics. Participants One hundred and ninety patients with long-term musculoskeletal conditions attending outpatient physiotherapy were recruited from seven physiotherapy clinics. Interventions Physiotherapy including disease-specific modalities and a general individually tailored exercise programme. Patients were evaluated at baseline and at the end of the programme. Main outcome measures International Physical Activity Questionnaire short form (IPAQ-sf) and COOP WONCA functional assessment charts. Results Forty-two patients were excluded from the analysis because they did not complete the IPAQ-sf correctly or dropped out during the treatment period. There was a significant increase in the number of metabolic equivalent task (MET)-min/week for vigorous and moderate-intensity activities, walking and total physical activity. The number of exercise sessions per week increased from 1.8 [standard deviation (SD) 0.9] to 2.2 (SD 1.2) (P = 0.001). The proportion of patients with a low level of physical activity decreased by 12%, and the proportion of the participants who did not/could not exercise decreased from 26% to 8%. The COOP WONCA charts showed significant improvements in the physical fitness, feelings, daily activities and social activities items. Conclusion A significant increase was found in the number of MET-min/week for all activity levels. Therefore, a general physical exercise programme initiated by a physiotherapist led to a positive change in level of physical activity.